The Effect of Internet Addiction, Materialism, Hedonic Shopping Motivation, and Promotion on Online Impulse Buying - Hajati, Dayat Ikhsan (Entrepreneurship Faculty, Universitas Garut, 2023)
This research aims to determine the influence of internet addiction, materialism, hedonic shopping motivation, and promotions on online impulse buying among the people of Kotabaru, both partially and simultaneously. This study took a sample of 385 people. The data analysis techniques used in this research are descriptive statistical analysis and multiple linear regression analysis. The results of this research show that, partially, there is one variable that does not have a significant effect on online impulse buying, namely the internet addiction variable, while the other three variables, namely the nature of materialism, hedonic shopping motivation and promotions, have a significant effect on online impulse buying. And simultaneously, there is a significant influence of all variables on online impulse buying with a large influence of 51.2% while the remaining 48% is determined by variations in changes in other variables which are not included in the research model.